Pengaruh Weld Time Terhadap Kecacatan Produk Pada Proses Pengelasan Material Termoplastik ABS (Akrilonitril Butadiena Stiren) Menggunakan Mesin Ultrasonic Welding - Benny Haddli Irawan; Fajar Putra Ryadi; Wowo Rosbandrio (Politeknik Negeri Batam, 2020)
The main problem that occurs in most ultrasonic welding processes on ABS thermoplastic materials using ultrasonic welding machines is improper parameter selection. Selection of incorrect parameters will cause various defects in the product such as gaps, dent, offside etc. One parameter that is very influential on the results of welds is the weld time parameter, it is because this parameter has a high level of sensitivity to the welding results. That is why the purpose of this research itself is to test the effect of weld time on the product produced by welding five different parameters starting from the minimum of 0.190s to the maximum parameter of 0.350s by using 15 samples that are available for later testing. parameters using 3 product samples to get maximum results. Then the inspection method used to determine the effect of the weld time parameter is the first air leak testing using a water leakage tester to ensure the weld results on the product there are no leaks and the second method is visual inspection assisted with a tool called luxo lamp, this tool is in the form of a magnifying glass illuminated lights so that we can easily ascertain what defects occur in the product after welding. The results of the data from this study are expected to indicate whether there is a significant influence of the weld time parameters on defects that occur in the product so that it can help companies overcome the problems that occur.